Portrait of young Georg Bredig - Noack, H. (1872)
A carte de visite of Georg Bredig (1868-1944) as a young child in what is today Głogów, Poland. From 1871 to 1919 the city was part of Germany. Young Bredig is posed standing among ornate furniture with a tyrolean hat sitting on a table beside him.
Keywords: Bredig, Georg, 1868-1944; Children